Coaliciones de turno: corrupción electoral y política competitiva en la Cataluña de la Restauración - Gemma Rubí i Casals (Mélanges de la Casa de Velázquez)
This article seeks to explain the nature of political «caciquism» in Restoration Catalonia based on an analysis of the destruction of the system of dynastic alternation, of the adaptation of the Catalanist, republican and Carlist oppositions to the rules of play in the Canovist system, and of the survival of governmental caciquism in the context of the emergence of mass politics and multi-party, competitive elections.